Pelatihan Pemanfaatan E-Commerce Dalam Meningkatkan Pendapatan Ekonomi Muslimah Masjid Darul Hannan - Nursobah; Ita Arfyanti (Forum Kerjasama Pendidikan Tinggi, 2021)
Every service activity carried out by lecturers is expected to help the community in facilitating the community in helping to increase economic income during this pandemic, this service aims to provide insight to Muslim women at the Darul Hannan Mosque where participants are teenagers to mothers who participate in the organization regarding the use of internet networks and social media, as for ways that can be done to improve the economy, namely by taking advantage of the availability of e-commerce in marketing various types of products and services, the stages carried out in a service are creating training forums such as workshops where the activity will explain the benefits of e-commerce. -commerce, scope and achievements of e-commerce, goals of e-commerce and participants are taught directly from account creation to transaction processing. This activity can be said to introduce communication media, technology and the ease of starting a business in the era of digital technology. The results obtained are the audience's knowledge of the type of e-commerce and the ease of use of e-commerce